Ownership Structure, Earnings Management and Investment Opportunity Set: Evidence from Mexican Firms - Juan M. San Martin-Reyna; Jorge A. Durán-Encalada (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This paper analyses the influence of ownership, board of directors, and financial leverage on companies’ performance when these either face, or do not face, profitable growth opportunities. Towards that end we examined a sample of 83 listed Mexican firms during the period 2005-2011. The results confirm the relevance of debt and board of directors in terms of firm market value by showing a negative relationship between performance and both, board of directors and leverage, in the presence of growth opportunities. In contrast, the relationship between debt and performance becomes positive when firms have no profitable investment projects. The results also demonstrate that the relevance of controlling shareholders on firm value is different when firms have or not growth opportunities. Therefore, our results show that ownership structure, composition and size of board and the level of leverage play a dual role on performance (increase or decrease the firm value) and determinewhether the firms have profitable investment projects.